1993
DOI: 10.1055/s-0038-1651605
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Acute Myocardial Infarction and rt-PA Therapy on Circulating Fibrinogen

Abstract: SummaryIn 12 patients treated with 100 mg rt-PA/3 h for acute myocardial infarction (AMI), serial fibrinogen levels were measured with the Clauss clotting rate assay (“functional fibrinogen”) and with a new enzyme immunoassay for immunologically intact fibrinogen (“intact fibrinogen”). Levels of functional and “intact fibrinogen” were strikingly different: functional levels were higher at baseline; showed a more pronounced breakdown during rt-PA therapy; and a rebound phenomenon which was not seen for “intact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…One remarkable finding of this study is that with both fibrates the ratio of functional fibrinogen to fibrinogen protein ("functionality" of fibrinogen) was decreased. Changes in the functionality of circulating fibrinogen have also been observed during acute myocardial infarction and subsequent thrombolytic therapy (27)(28)(29). Seifried et al (27) ascribed these changes in functionality to an altered distribution of the three molecular weight forms of fibrinogen in plasma, forms which have different clotting behaviour (30,31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One remarkable finding of this study is that with both fibrates the ratio of functional fibrinogen to fibrinogen protein ("functionality" of fibrinogen) was decreased. Changes in the functionality of circulating fibrinogen have also been observed during acute myocardial infarction and subsequent thrombolytic therapy (27)(28)(29). Seifried et al (27) ascribed these changes in functionality to an altered distribution of the three molecular weight forms of fibrinogen in plasma, forms which have different clotting behaviour (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the functionality of circulating fibrinogen have also been observed during acute myocardial infarction and subsequent thrombolytic therapy (27)(28)(29). Seifried et al (27) ascribed these changes in functionality to an altered distribution of the three molecular weight forms of fibrinogen in plasma, forms which have different clotting behaviour (30,31). During the initial phase of acute myocardial infarction the relative amount of the fast-clotting HMW fibrinogen in the total fibrinogen content is increased, explaining tr L 0 at least in part the relatively high functional fibrinogen levels in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibrinogen is synthesized as the high molecular weight species (HMW-fibrinogen), with a high phosphorous content (6)(7)(8)(9)(10). Newly synthesized fibrinogen is highly thrombogenic because the high content of HMW-fibrinogen produces an increase in fibrinopeptide release and in fibrin polymerization, and the thrombi formed have a tight, rigid, and space-filling fibrin network (7)(8)(11)(12)(13)(14). It has been observed that the early rates of phosphorylated fibrinopeptide A and fibrinopeptide A release are higher in newly synthesized HMW-fibrinogen with its higher phosphorous content, than in HMW-fibrinogen with a normal phosphorous content (8).…”
Section: Introductionmentioning
confidence: 99%